Price Promotion and Ease of Use on Generation Z Impulsive Buying through Fear of Missing Out - Sastra Mico (Global Academy of Business Studies, 2026)
Purpose: This study develops and explains a conceptual model of how price promotion and application ease of use influence impulsive buying among Generation Z e-commerce users, with the Fear of Missing Out (FoMO) acting as an intervening variable that links marketing and technological stimuli to spontaneous purchasing. Research Methodology: This study uses an integrative literature review. Peer-reviewed articles on price promotion, technology acceptance, FoMO, and impulsive buying were collected, compared, and synthesized to construct a theoretical framework and a set of testable propositions, together with a proposed measurement model for future empirical validation using partial least squares structural equation Modeling. Results: A four-path model was synthesized. Price promotion is proposed to raise FoMO; application ease of use and FoMO are each proposed to increase impulsive buying; and FoMO is proposed to mediate the effect of price promotion on impulsive buying. Conclusions: FoMO functions as a central psychological mechanism that converts promotional and technological stimuli into unplanned purchases among young digital consumer. Limitations: The model is conceptual and has not yet been validated using primary data. Contributions: This study connects the Technology Acceptance Model with FoMO research and offers a ready framework for empirical testing, alongside practical guidance for e-commerce managers and consumer-protection scholars.